An Enhanced Johnson–Cook Model for Hot Compressed A356 Aluminum Alloy. Issue 1 (13th September 2020) - Chen, Xiao-Min; Lin, Y. C.; Hu, Hong-Wei; Luo, Shun-Cun; Zhou, Xiao-Jie; Huang, Yi
Abstract : The isothermal compression experiments with the strain rates of 0.01–10 s −1 and deformation temperature range of 300–420 °C are performed to investigate the hot deformation behavior of A356 aluminum alloy. Also, the complex deformation mechanisms are analyzed. It is found that, as the strain is gradually increased, the flow stress first rises, and then the stable stress appears without a tangible peak. The microstructures exhibit large elongated grains, and only a few small new grains appear under most deformation conditions. It is because the dynamic recovery (DRV) is the dominant softening mechanism. Based on the measured data, both the original Johnson–Cook (O–JC) model and modified Johnson–Cook model (M–JC) are built for the tested aluminum alloy. However, there are different deviations between the experimental and the predicted true stresses by O–JC model and M–JC model. Considering the obvious DRV features, an enhanced Johnson–Cook (EH–JC) model is proposed by introducing the stress–dislocation relation. The accuracy of the EH–JC model is validated because the correlation coefficient between the experimental and predicted results is as high as 0.997, whereas the average absolute relative error is merely 2.84%. Abstract : The hot compressive deformation behaviors of A356 aluminum alloy are studied. The main softening mechanism is dynamic recovery. Both the original Johnson–Cook model and modified Johnson–Cook model are built, but they cannot accurately describe the hot deformation behavior. Considering the obvious DRV feature, an enhanced Johnson–Cook model is proposed and validated.